Convergence of Solutions to a Certain Vector Differential Equation of Third Order - Cemil Tunç; Melek Gözen (Abstract and Applied Analysis)
We give some sufficient conditions to guarantee convergence of solutions to a nonlinear vector differential equation of third order. We prove a new result on the convergence of solutions. An example is given to illustrate the theoretical analysis made in this paper. Our result improves and generalizes some earlier results in the literature.